Acute Abdomen Resulting from Concurrent Thrombosis of Celiac Trunk and Superior Mesenteric Artery - Savaş Bayrak; Hasan Bektas; Yigit Duzkoylu; Ayhan Guneyi; Ekrem Cakar (Case Reports in Gastrointestinal Medicine)
Mesenteric ischemia is one of the most mortal diseases of the gastrointestinal system causing acute abdomen. In most of the patients, the etiological factor is the obstructive embolism or thrombosis of superior mesenteric artery. In the literature, there have been reports regarding also celiac trunk occlusion in rare situations. The gold standard treatment relies on early diagnosis. The originality of our report relies on the concurrent obstruction of both vascular structures.